2021
DOI: 10.1039/d1nr00150g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene ink for 3D extrusion micro printing of chemo-resistive sensing devices for volatile organic compound detection

Abstract: Printed electronic sensors offer a breakthrough in the availability of low-cost devices for improving quality of human life. Conductive ink is the core of printing technology and one of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…, acetone, ethanol, and methanol). In particular, the device showed a high sensitivity towards ethanol ( Hassan et al, 2021 ). These case study results suggest that Cyrene based graphene inks are more stable and suitable than the currently employed solvents for commercial applications, without any toxicity issues.…”
Section: Case Study: Cyrene As the Most Advanced Green Solvent For Lp...mentioning
confidence: 99%
“…, acetone, ethanol, and methanol). In particular, the device showed a high sensitivity towards ethanol ( Hassan et al, 2021 ). These case study results suggest that Cyrene based graphene inks are more stable and suitable than the currently employed solvents for commercial applications, without any toxicity issues.…”
Section: Case Study: Cyrene As the Most Advanced Green Solvent For Lp...mentioning
confidence: 99%
“…The emergence of solution processed 2D materials and ink formulation 43,44,47,49,50,[64][65][66] has enabled their value-added harnessing into established coating and printing technologies, offering the promise of their automatised (i.e., consistent), scalable manufacturing and device integration (e.g., (opto)electronics, photonics, energy storage, sensing, etc.). 44,67 Coating and printing technologies, including spray coating, 68 inkjet printing, 69 and extrusion-based 3D printing, 70 have evolved to implement 2DMs-based device manufacturing with high homogeneity and resolution, by adapting their printing components and processes to 2DMs inks. 47 In parallel, since the first example of inkjet-printed graphene-based flexible electronics reported in 2011, 71 sustainable progress (e.g., shift to non-toxic, volatile solvents, conscious choice and use of additives and binders, etc.)…”
Section: Coating and Printing Technologies-based Heterostructure Fabricationmentioning
confidence: 99%
“…[17][18][19] For instance, Hassan et al demonstrated that extruded 3D printed graphene ink-based sensors exhibited a wide detection concentration range (5-100 ppm) and excellent selectivity for methanol, ethanol, and acetone at room temperature. 20 In addition to the excellent properties of graphenebased nanomaterials, intentional incorporation of heteroatoms such as nitrogen or boron is known to endow graphene with a wide spectrum of new properties. [21][22][23] Most importantly, co-doping of graphene with boron (B) and nitrogen (N) atoms has been shown to provide graphene with inter-changeable p-and n-type semiconducting properties, which are dependent on their bonding states and doping levels.…”
Section: Introductionmentioning
confidence: 99%